Implementation of Multimedia Project-Based Learning Model and Language Attitude towards Writing Skills - Amalia, Husnil; Effendi Thahar, Harris (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The implementation of learning skills in writing review texts is still oriented toward completing the tasks given by the teacher. This results in students needing help developing review text writing skills. This research examines how implementing a multimedia-based Project-Based Learning learning model and language attitudes affects students' review text writing skills in class VII SMP. Classified as a type of quantitative research, this research applies an experimental method with a 2×2 factorial design. The sample was taken from the entire population, namely class VII.1 was chosen as the experimental class, and class VII.2 was chosen as the control class with 60 students. Based on the analysis and discussion results, the multimedia-based project-based learning model is proven to improve learning outcomes for students' review of text writing skills compared to conventional learning models. The multimedia-based project-based learning model provides a basis for reflecting on effective teaching methods. These results indicate that involving students in multimedia projects can stimulate creativity and strengthen their understanding of writing concepts. Apart from that, this study's results confirm no interaction between the multimedia-based Project-based Learning learning model and language attitudes.